Contextual Positive Psychology: Policy Recommendations for Implementing Positive Psychology into Schools - Ciarrochi, Joseph; Atkins, Paul W. B.; Hayes, Louise L.; Sahdra, Baljinder K.; Parker, Philip (Frontiers in Psychology, 2016)
There has been a rapid growth in positive psychology, a research and intervention approach that focuses on promoting optimal functioning and well-being. Positive psychology interventions are now making their way into classrooms all over the world. However, positive psychology has been criticized for being decontextualized and coercive, and for putting an excessive emphasis on positive states, whilst failing to adequately consider negative experiences. Given this, how should policy be used to regulate and evaluate these interventions? We review evidence that suggests these criticisms may be valid, but only for those interventions that focus almost exclusively on changing the content of people’s inner experience (e.g., make it more positive) and personality (improving character strength), and overemphasize the idea that inner experience causes action. We describe a contextualized form of positive psychology that not only deals with the criticisms, but also has clear policy implications for how to best implement and evaluate positive education programs so that they do not do more harm than good.